The utilization of selective neck dissection in the treatment of recurrent branchial cleft anomalies. Issue 33 (August 2019) - Li, Linke; Liu, Jun; Lv, Dan; Shen, Tian; Deng, Di; Wang, Ji; Chen, Fei
Abstract : Abstract: To investigate the characteristics of recurrent branchial cleft anomalies (BCAs) and to evaluate the surgical technique and outcomes of patients undergoing reoperation. From January 2005 to August 2018, the clinical data of 216 patients with recurrent second, third, and fourth BCAs were retrospectively analyzed. According to the embryological and anatomical features of the cleft palate and recurrence site, selective neck dissection techniques were used for surgical treatment. Among all 216 patients, 203 healed by primary healing. Twelve patients with local infections and 1 patient with a pharyngeal fistula healed after dressing changes. Eleven patients experienced transient hoarseness and recovered after a few months. Three patients developed permanent hoarseness, and 5 patients developed coughing after eating and drinking. Three patients underwent internal jugular vein ligation. Only 4 recurrences occurred during a follow-up period of more than 1 year. The total cure rate was 98.15%. Selective neck dissection is an effective and safe surgical treatment for recurrent second, third, and fourth branchial cleft anomalies.